A 3-month Safety Assessment of Human Bone Marrow Derived Mesenchymal Stromal Cells Administered Once by the Intramuscular Route to Immunodeficient Mice. (April 2018) - Creane, Michael; McElroy, Mary; Duffy, Aoife; Dawood, Chaansha Shaik; O'Brien, Timothy
Critical limb ischemia (CLI) represents the severest manifestation of peripheral arterial disease and is a major unmet medical need. This disease occurs when the arterial blood supply within the limb fails to meet the metabolic demands of the resting muscle or tissue, resulting in chronic ischemic rest pain and/or tissue necrosis. Human mesenchymal stromal cells, termed hMSCs, represent an exciting therapeutic modality for the treatment of this disease due to their immunomodulatory and tissue reparative functions. The aim of the study was to assess the preclinical toxicity profile of human bone marrow–derived MSCs in support of their use as a treatment for CLI. A 3-month toxicity study was carried out under good laboratory practices in immunodeficient mice who received, intramuscularly, a single dose of 3 × 10 5 (approximately 15 × 10 6 cells/kg) hMSCs manufactured under good manufacturing practices. No significant changes in body weight, food consumption, clinical signs, or histopathological changes were observed in the hMSC-treated mice in comparison to the controls. These results highlight that the administration of hMSCs during the 3-month study period was well tolerated and not associated with any test item–related tumors. This data set supported the initiation of a phase 1b first in human study in "no option" for revascularization patients with CLI.